A non-smooth quasi-zero-stiffness isolator with displacement constraints. (1st July 2022) - Zeng, Rong; Yin, Shan; Wen, Guilin; Zhou, Jiaxi
Highlights: A novel double-layer quasi-zero-stiffness isolator is designed by introducing displacement constraints. The approximation approach and incremental harmonic balance method are used to solve dynamic equations of the proposed non-smooth system. Compared with traditional isolators, the proposed non-smooth isolator can exhibit superior isolation performance. The increasing displacement feedback gain can significantly broaden the vibration-isolation range of the proposed non-smooth isolator at low frequency. Abstract: Quasi-zero-stiffness (QZS) mechanism is one of the significant solutions with its distinct advantage to the low-frequency vibration isolation problems in mechanical vibration. However, subject to the limitation of its effective range of very narrow, the strong nonlinearity of the single QZS mechanism under large-amplitude excitation might induce an undesirable large-amplitude vibration or even damage some essential equipment. Therefore, this paper designs a double-layer QZS vibration isolator with displacement constraints to reduce the undesirable large-amplitude vibration. Firstly, the mechanical model of a double-layer QZS vibration isolator with displacement stops is established based on Hertz's contact model (DLQZS-HCM). Subsequently, the incremental harmonic balance method is employed to examine the vibration isolation performance theoretically. The system parameters are then analyzed to explore their influences on the isolation performance. Compared with the double-layer linear isolator (DLL) and double-layer QZS isolator (DLQZS), it is found that the DLQZS-HCM isolator can perform better in both extending the frequency range of vibration isolation and decreasing the peak transmissibility when undergoing large-amplitude excitation. Finally, in order to further enhance the isolation performance at low-frequency levels, feedback control is applied to the DLQZS-HCM isolator. The obtained results reveal that the increasing displacement feedback gain can significantly broaden the vibration-isolation range of the DLQZS-HCM isolator in the frequency area tending to zero. Graphical Abstract: Image, graphical abstract